KEBERAGAMAN DAN EKSKLUSI SOSIAL: SIMBOL IDENTITAS DALAM RUANG PUBLIK - Setyawati, Lugina (Jurnal Masyarakat dan Budaya, 2010)
This article is a writing based on a research on tolerance and diversity in Tangerang City. The objectives of this writing is to describe social relations between groups with different ethnic and religious backgrounds by unfolding and reflecting boundaries of identity built by these groups. This writing argues that decentralization as a context, in which tolerance, ethnic identity and democratization has worked as a new arena for repositioning and redefintion the relations between groups at local level. The State (in this particular is the Local Government) is actually play a role as an agent that reconstructs the relations between ethnic and religious groups; and some of their “policies” has created social exclusion in public spaces. As the research unfold, Tangerang’s City vision to build “akhlaqul karimah” society (a society with pious religious attitudes), has contibuted to the shaping of social relations of the groups with different ethnic and religious backgrounds that shares living spaces in Tangerang, as the local government tries to “color” the city identity by expressing certain religious symbols in open public spaces. The result is a form of social exclusion, experienced and felt by ethnic (and religious) groups, which are the minority in political, economical and socio-cultural arena in Tangerang City. Keywords: social exclusion, Tangerang City vision, identity symbols in public spaces